Risk of Second Primary Malignancies in Colon Cancer Patients Treated With Colectomy - Zhang, Bo; Guo, Kaibo; Zheng, Xueer; Sun, Leitao; Shen, Minhe; Ruan, Shanming (Frontiers in Oncology, 2020)
Background: Second primary malignancy (SPM) attracts a growing attention. However, the clinical features of colon cancer (CC) survivors with SPMs are not clear and could help guide clinicians to develop a better surveillance strategy. Methods: We reviewed 56,930 CC survivors treated with colectomy from the Surveillance, Epidemiology, and End Results (SEER) database during 1998–2011. Competing risk models and nomograms were conducted for predicting the risk of occurring SPMs. The clinical utility of the models was measured by decision curve analysis (DCA) using net benefit approaches. Results: 5013 (17.1%) of male patients developed SPMs and sites of SPMs included prostate (32.2%), lung and bronchus (11.6%), urinary bladder and kidney (10.8%), colon (10.0%) and melanoma of the skin (3.9%), while 3592 (13.0%) of female patients occurred SPMs and sites of SPMs involved breast (25.8%), lung and bronchus (13.6%), colon (11.6%), uterus (8.2%), urinary bladder and kidney (5.6%). Survivors with a second carcinoma of lung and bronchus showed the worst prognosis. Older age increased the risk of SPMs in both male (Subdistribution hazard ratio =2.85 [95% confidence interval=2.53-3.21]) and female (1.80 [1.59-2.04]) survivors, especially for the risk of a second prostate carcinoma in male (5.33 [4.03-7.03]). Compared with white race, black male survivors remained at higher risk to develop the second prostate carcinoma (1.98 [1.74-2.26]). Competing-risk nomograms for CC survivors were established to help clinicians predict the probabilities of overall SPMs and prostate carcinoma. Validation of nomograms showed good discrimination and accuracy, and DCAs revealed the clinical effectiveness. Conclusions: We profiled the clinical characteristics of a large population-based cohort of CC survivors. These features may improve future follow-up management.